2023
DOI: 10.1177/09544070221145512
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial laser cladding of cobalt-base alloy StelliteTM 6 on gray cast iron/investigations on friction, wear versus commercial brake pad, and corrosion characteristics

Abstract: Environmental legislation and the electrification of vehicles place increased requirements on brake disks in terms of wear and corrosion resistance. Departing from a preliminary study, the present investigation examined the friction and wear behavior as well as the corrosion properties of Stellite™ 6 coatings on gray cast iron, which were deposited by laser cladding. The friction and wear experiments were conducted on a pin-on-disk tribometer at contact pressures of 1.0 and 2.0 MPa as well as rotation speeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…As an example, Chioibasu et al [ 70 ] reported that the corrosion rate of gray cast-iron brake discs coated with Inconel 718 by direct energy deposition was significantly lower than that of the bare discs. A similar effect is reported also for stellite coatings on gray cast-iron brake discs [ 71 ].…”
Section: Approaches To Control Corrosion Stiction In Braking Systemssupporting
confidence: 83%
“…As an example, Chioibasu et al [ 70 ] reported that the corrosion rate of gray cast-iron brake discs coated with Inconel 718 by direct energy deposition was significantly lower than that of the bare discs. A similar effect is reported also for stellite coatings on gray cast-iron brake discs [ 71 ].…”
Section: Approaches To Control Corrosion Stiction In Braking Systemssupporting
confidence: 83%
“…This higher corrosion resistance is attributed to the formation of strong Cr and Co oxide films in the hardfaced stellite specimens and it is identical to the previous findings. [62][63][64][65][66][67] Stellite-6 is an excellent corrosion resistance material because of the high-chromium content, enabling it to form a strong oxide film on the surface. [65,68] The passive film formed on the stellite-6-deposited specimen is stable, while the substrate underwent severe corrosion damage and the electrochemical characteristics confirm the corrosion trend.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…The increase in pitting resistance of hardfaced stellite-6 specimen is mainly confirmed by the fraction of Cr, W, and Co fraction from SEM-EDS analysis. [66,67] Further, the overlapped portion of the overlays offers excellent corrosion resistance because of the remelting phenomenon. [72] From the micrographs, it is clear that the pitting is severe at the substrate side.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…In this study, voc palm kernel brake are compared to asbestos-containing industrial brake pads. [7] In light of the current state of research, the following objectives have been established for the scope of this study • Development of Break pad using PKS powder, epoxy resin, carbon, Aluminium oxide, Hardener, and calcium carbonate.…”
Section: Introductionmentioning
confidence: 99%